(untitled) (Analytical Methods for Drug Development, 2025)
Author Miss Chaudhari Sakshi Dattatraya UG Scholar, Sharadchandra Pawar College of Pharmacy, Dumbarwadi, Otur, Pune, Maharashtra, India Abstract Physical characterization techniques assess critical solid pharmaceutical properties that directly impact drug performance. Particle size analysis uses laser diffraction, dynamic light scattering, microscopy, and sieving to measure size distributions that influence bioavailability, stability, and manufacturing processes. Surface area determination through gas adsorption and BET theory quantifies available surface area, predicting dissolution rates and quality attributes across various dosage forms. Powder X-ray diffraction identifies crystalline structures, distinguishes polymorphs, and monitors solid-state stability through diffraction pattern analysis. Microscopy techniques including optical, electron, and atomic force methods visualize morphology, surface features, and particle characteristics at increasing magnification levels. These complementary techniques create comprehensive understanding of pharmaceutical materials by measuring fundamental physical properties. Results directly correlate with critical quality attributes including bioavailability, stability, and manufacturability. Keywords: Particle Size, Surface Analysis, Crystallinity, Particle Characterization, Solid-State Stability VIEW PDF